Mapping for Halal Certification Process Optimization in the Context of Logistics Companies in Indonesia - Wynd Rizaldy; Prasadja Ricardianto; Sita Aniisah Sholihah; Bagus Sumargo (Jurnal Ilmu Multidisiplin, 2025)
This study aims to map for Halal Certification process optimization in the context of logistics companies in indonesia through LPPOM MUI (Institute for the Assessment of Food, Drugs and Cosmetics of the Indonesia Ulema Council) qq (Qualitate Qua) BPJPH (Halal Product Assurance Agency) in the issuance of halal logistics certificates. This study uses a mix method using 2 stages that the researcher calls the SD (Systematic and Dynamics) Model, starting with the initial stage in the form of a qualitative approach with literature review on several reputable journal databases through SLR Analysis (Systematic Literature Review) with the results of 38% or 27 out of 71 articles in Scopus journals and the theory used to form variables and indicators. Furthermore, using System Dynamics Analysis assisted by Vensim software, a research model was obtained that was displayed with CLD (Causal Loop Diagram) and SFD (Stock Flow Diagram).